Web Information Systems Engineering - WISE 2008 9th International Conference, Auckland, New Zealand, September 1-3, 2008, Proceedings - Bailey, James; Maier, David; Schewe, Klaus-Dieter; Thalheim, Bernhard; Wang, X. Sean (Information Systems and Applications, incl. Internet/Web, and HCI ;, 2008)
This book constitutes the proceedings of the 9th International Conference on Web Information Systems Engineering, WISE 2008, held in Auckland, New Zealand, in September 2008. The 17 revised full papers and 14 revised short papers presented together with two keynote talks were carefully reviewed and selected from around 110 submissions. The papers are organized in topical sections on grid computing and peer-to-peer systems; Web mining; rich Web user interfaces; semantic Web; Web information retrieval; Web data integration; queries and peer-to-peer systems; and Web services.